The interplay between climatic niche evolution, polyploidy and reproductive traits explains plant speciation in the Mediterranean Basin: a case study in Centaurium (Gentianaceae) - Valdés-Florido, Ana; Valcárcel, Virginia; Maguilla, Enrique; Díaz-Lifante, Zoila; Andrés-Camacho, Cristina; Zeltner, Louis; Coca-de-la-Iglesia, Marina; Medina, Nagore G.; Arroyo, Juan; Escudero, Marcial (Frontiers in Plant Science, 2024)
Speciation and diversification patterns in angiosperms are frequently shaped by niche evolution. Centaurium Hill is a Mediterranean genus with ca. 25 species, of which 60% are polyploids (tetra-and hexaploids), distributed mainly in the Mediterranean Basin and in areas with temperate and arid climates of Asia, Europe, North-Central Africa and North America.The evolutionary history of this genus has been studied using morphological, biogeographical and molecular approaches, but its climatic niche characterization and its relation with genome evolution (chromosome number and ploidy level) has not been addressed yet. Thus, this study aims to identify the role of the evolution of climatic niche, ploidy level, life cycle and floral traits in the diversification of Centaurium. Climatic niche characterization involved estimating present climate preferences using quantitative data and reconstructing ancestral niches to evaluate climatic niche shifts. The evolution of climatic niche towards selective optima determined by ploidy level (three ploidy levels) and different binary traits (polyploidy, floral size, floral display, herkogamy and life cycle) was addressed under the Ornstein-Uhlenbeck model. Chromosome number evolution was inferred using the ChromoSSE model, testing if changes are clado-or anagenetic. Chromosome number evolution and its link with cladogenesis, life cycle and floral traits was modeled on the phylogeny. The reconstruction of the ancestral niches shows that Centaurium originated in a mild climate and diversified to both humid and cold as well as to dry and warmer climates. Niche conservatism was estimated in the climatic niche of the ancestors, while the climatic niche of the current taxa experienced transitions from their ancestors' niche. Besides, the evolution of climatic niche towards multiple selective optima determined by the studied traits was supported, life cycle optima receiving the highest support. The reconstruction of chromosome number transitions shows that the rate of speciation process resulting from chromosomal changes (chromosomal cladogenesis) is similar to that of non-chromosomal cladogenesis. Additionally, dependent evolution of floral size, floral display and herkogamy with chromosome number variation was supported. In conclusion, polyploidization is a crucial process in the Mediterranean region that assisted speciation and diversification into new areas with different climates, entailing niche shifts and evolution of reproductive strategies.